Analisis Semiotika Terhadap Tokoh Utama Perempuan dalam Film Perempuan Tanah Jahanam - Samanda, Glen Aviaro; Kusuma, Ade (Az-Zahra: Journal of Gender and Family Studies, 2023)
Horror is still a popular genre in the growth of Indonesian films. Female characters are often featured iconically in the narrative of a horror film. However, there is a negative stigma about the presence of female characters in horror films who appear as antagonistic characters. Female characters often play the role of ghosts, victims of crimes, and other complementary characters. This study uses qualitative research and Roland Barthes semiotics to analyze the representation of female characters in Perempuan Tanah Jahanam. This research focuses on the main female characters in the movie. The results of this study explain the denotation that describes the female characters in Perempuan Tanah Jahanam as women who become the main characters in filling various important roles in horror films, while in the connotation there are various meanings that the main female characters have social strengths such as courage in fighting patriarchal culture, supporting fellow women, working hard and being independent, from the denotation and connotation that the author found formed a myth in the form of elements of feminism that were constructed on the four main characters in the film. Researchers found that the main female character is no longer represented as a victim or a seductive and sexy ghost. Female characters are also not used as a means of supporting the success and interests of commercialism in a horror film.